1997
DOI: 10.1037/1076-8971.3.2-3.402
|View full text |Cite
|
Sign up to set email alerts
|

Commonsense rape judgments: An empathy–complexity theory of rape juror story making.

Abstract: The study of juror judgment in cases of rape has been a staple of social psychology research for nearly 25 years. However, the literature on attribution of responsibility to rape victims has been confusing and contradictory. This literature is first reviewed and then reinterpreted in light of recent advances in social cognition research and theorizing that has been specifically focused on "commonsense" legal judgments. We then offer an extension of the story model (N. Pennington & R. Hastie, 1986Hastie, , 1991… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 127 publications
(163 reference statements)
1
35
0
2
Order By: Relevance
“…Consistent with greater prevalence rates of female victimization and male perpetration (Rape, Abuse and Incest National Network 2009; Rozee and Koss 2001;U.S. Department of Justice 2008), women can more easily understand and identify with victims than men (Deitz and Byrnes 1981;Deitz et al 1984;Olsen-Fulero and Fulero 1997). Likewise, men may be more able than women to understand and identify with perpetrators of rape.…”
Section: Rape Empathy and Gendermentioning
confidence: 80%
See 1 more Smart Citation
“…Consistent with greater prevalence rates of female victimization and male perpetration (Rape, Abuse and Incest National Network 2009; Rozee and Koss 2001;U.S. Department of Justice 2008), women can more easily understand and identify with victims than men (Deitz and Byrnes 1981;Deitz et al 1984;Olsen-Fulero and Fulero 1997). Likewise, men may be more able than women to understand and identify with perpetrators of rape.…”
Section: Rape Empathy and Gendermentioning
confidence: 80%
“…Theory and research on empathy has also suggested that similarity to a target victim, exposure to a target victim, and personal victimization experience are factors that may increase identification with, understanding of and empathy with a victim (Barnett et al 1987;Batson and Shaw 1991;Cialdini et al 1997;Deitz et al 1982;Deitz and Byrnes 1981;Deitz et al 1984;Krebs 1975;Olsen-Fulero and Fulero 1997;Schewe and O'Donohue 1993). Consistent with greater prevalence rates of female victimization and male perpetration (Rape, Abuse and Incest National Network 2009; Rozee and Koss 2001;U.S.…”
Section: Rape Empathy and Gendermentioning
confidence: 87%
“…A primeira se centra no estudo dos processos cognitivos de tomada de decisão dos jurados e o segundo na dinâmica de deliberação do grupo de jurados. Sobre o processo individual de decisão dos jurados os autores argumentam que o modelo de explicação ou modelo da história (Levett, Danielsen, Kovera, & Cutler, 2005;Olsen-Fulero & Fulero, 1997;Pennington & Hastie, 1992) tem trazido contribuições significativas e evidências empíricas recorrentes para explicar como os jurados compreendem, relembram e utilizam as evidências apresentadas pelas partes para definir o seu parecer no caso. Este modelo postula que os jurados procuram organizar todos os elementos observados em uma estrutura sumarizada, na qual capturam qual é a verdade sobre o caso.…”
Section: Psicologia Social E Leiunclassified
“…No contexto específico da deliberação de juízes leigos, a pesquisa já produziu modelos que auxiliam na explicação do processo de deliberação (Olsen-Fulero & Fulero, 1997;Pennington & Hastie, 1992), como já foi apresentado anteriormente neste artigo. Tais modelos foram desenvolvidos em outro contexto cultural e judicial, o que implica na necessidade de pesquisas brasileiras que compreendam como se dão estes processos de tomada de decisão de jurados em nosso contexto judicial.…”
Section: Processos Sócio-cognitivos E Deliberação Dos Juradosunclassified
“…The three self-report self-referencing measures, which asked how much participants had thought about what they would have thought, felt, and done had they found themselves in the defendant's situation, became the three indicators for a latent self-referencing measure in the tested model (see Figure 11). According to some research (e.g., Jones & Nisbett, 1972;Krebs, 1975;Olsen-Fulero & Fulero, 1997), jurors' perceived situational and personal relevance to the actors involved in a trial will influence whether and to what extent they take the perspective of and self-reference to those actors.…”
Section: Materials and Proceduresmentioning
confidence: 99%